Implementation of Guided Inquiry Learning Model to Science Process Skills in Junior High School - Yuliani, Tri; Marjanah, Marjanah; Setyoko, Setyoko (Universitas Sultan Ageng Tirtayasa, 2023)
This study aimed to determine how students' science process skills are by applying a guided inquiry learning model to the material of the interaction of living beings to the environment at one of the junior high schools at Langsa city, Indonesia. The type of research used is experimental research with the form of pre-experimental design, and the research design is one shot case study. The results showed the highest percentage value of science process skills in the observation/observing indicator, namely obtaining a score of 78.95% with the